Ultrafast charge redistribution in small iodine containing molecules. (28th March 2019) - Hollstein, M; Mertens, K; Klumpp, S; Gerken, N; Palutke, S; Baev, I; Brenner, G; Dziarzhytski, S; Meyer, M; Wurth, W; Pfannkuche, D; Martins, M
Abstract: We present studies on intra-molecular charge redistribution in iodine containing molecules upon iodine-4d photoionization. For this, we employed an XUV-pump-XUV-probe scheme based on time-delayed femtosecond pulses delivered by the free-electron laser at DESY in Hamburg (FLASH). The experimental results show delay dependent and molecule-specific iodine charge state distributions that arise upon multiple iodine-4d photoionization. Using the example of CH3 I and CH2 I2, we compare the delay-dependent yields of I 3+ . We model the involved processes using advanced ab initio electronic structure calculations which include electron correlations combined with a classical model of the nuclear motion. The qualitative agreement of our model with the experimental results allows us to relate the observed, strongly molecule-specific efficiencies of the intra-molecular charge rearrangement not only to molecule-specific fragmentation timescales but also to molecule-specific electronic structure and molecular environment.